THE ROLE OF MSMES IN SUPPORTING THE INDEPENDENCE OF ISLAMIC BOARDING SCHOOLS - Dwi Sulastri; Achmad Firdaus (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study aims to analyze the factors influencing the success of Islamic Boarding School-based MSMEs and their impact on the economic independence of Islamic boarding schools. The research employs Structural Equation Modeling (SEM) to examine the relationships between the independent variables—human resources, leadership, technology utilization, access to capital, and networks/partnerships—and the dependent variable, MSME success, which is further analyzed for its effect on pesantren independence. Data were collected through a survey of 472 respondents consisting of MSME actors within Islamic Boarding School environments. The analysis reveals that human resources, access to capital, and networks/partnerships significantly influence MSME success, while leadership and technology utilization show no significant impact. Furthermore, MSME success contributes positively and significantly to enhancing the economic independence of Islamic Boarding Schools. This study provides theoretical contributions by enriching the literature on the role of MSMEs in supporting the economic independence of Islamic Boarding Schools. It also offers practical recommendations for effective management strategies to improve competitiveness and institutional self-reliance.